2005
DOI: 10.2337/diabetes.54.1.243
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Pigment Epithelium-Derived Factor Is Involved in the Pathogenesis of Diabetic Nephropathy

Abstract: Pigment epithelium-derived factor (PEDF) is a potent angiogenic inhibitor. Previous studies have shown that decreased ocular levels of PEDF are associated with diabetic retinopathy. However, the implication of PEDF expression in diabetic nephropathy has not been revealed. In the present study, we demonstrated for the first time that the expression of PEDF was decreased at both the mRNA and protein levels in the kidney of diabetic rats, whereas transforming growth factor-␤ (TGF-␤) and fibronectin levels were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 38 publications
6
85
1
Order By: Relevance
“…These differences likely reflect tissue-specific PEDF gene expression, whereby the liver had the highest expression levels, whereas those in the pancreas were low. 44 Other studies 7,45,46 indicate significant PEDF production by organs, such as the kidney and adipose tissue, and suggest that an increased distribution may occur under inflammatory conditions, such as obesity. Given PEDF's role in ameliorating tissue fibrosis, the contribution of other organs may be reflected in circulating systemic levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences likely reflect tissue-specific PEDF gene expression, whereby the liver had the highest expression levels, whereas those in the pancreas were low. 44 Other studies 7,45,46 indicate significant PEDF production by organs, such as the kidney and adipose tissue, and suggest that an increased distribution may occur under inflammatory conditions, such as obesity. Given PEDF's role in ameliorating tissue fibrosis, the contribution of other organs may be reflected in circulating systemic levels.…”
Section: Discussionmentioning
confidence: 99%
“…10 The antifibrogenic properties of PEDF have also been demonstrated in other organs, including the kidney, heart, and eye. 7,8,18,19 PEDF delivery ameliorated kidney fibrosis and proteinuria by suppressing transforming growth factor (TGF)-␤1 expression in diabetic rats. 8 Similarly, in a model of acute myocardial infarction, PEDF infusion reduced cardiac fibrosis through down-regulation of TGF-␤1 and fibrillar collagen expression, thereby improving left ventricular ejection.…”
mentioning
confidence: 99%
“…PEDF, which has anti-oxidant, anti-inflammatory and anti-angiogenic effects, has been closely associated with diabetic vascular disease, particularly retinopathy [13,14]. Plasma PEDF levels are increased in metabolic syndrome [18] and in type 1 and type 2 diabetes in the presence of complications [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in non-diabetic women indicated that rising serum endoglin and sFlt1/PlGF ratio herald the onset of pre-eclampsia [7]. Pigment epithelium-derived factor (PEDF), a novel anti-angiogenic protein, is also altered in diabetes and its increased serum levels are associated with diabetic vascular complications [13,14]. Although it is unclear whether PEDF is released from placental tissues in pre-eclampsia, PEDF could be implicated as a maternal risk factor in the pathogenesis of pre-eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Primary human glomerular mesangial cell (HMC) culture was described previously (31). Cells of passages 6 to 10 were used in the experiments.…”
Section: Cell Culturementioning
confidence: 99%